Build Web-Based Medical Record Application at Palembang Treatment Clinic in Magetan, East Java - Lermatin, Egen Endo; Rahmawati, Endra; Kartikasari, Puspita (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The treatment clinic located at Jl. Dr.Soetomo 2A Kelurahan Tawanganom, Magetan District in engaged in the field of services namely the field of treatment. Currentyly handling patient medical record is still manual that doctors note by hand every result of examination of patient medical record data in status folder until the note by hand every result of examination of patient medical record data in status folder until the note become one bundl. When doctors want to see the progress of the patient beforehand should look for one by one history of patients in one bundle and convey to the patients in one bundle and convey to the patient to take a long time. Another problem encountered is the vulnerability of loss of medical record data caused by negligence of the officer in the store od damaged when needed. Loss of patient medical records makes it difficult for physicians to determine medical measures. Given these problems, Klinik Palembang Treatment requires an application that can provide solutions to help solve problems by designing a web-based medical record application. This medical record application features a menu of registration process, patient recording, prescription recording, and drug payment. With the application is expected to facilitate the Clinic Treatment Palembang to see the development of patients to drug service.